Design, modelling and characterisation of a magnetic variable stiffness mechanism - Lim, Zhen Yi (2019)
The development of VIA has gained prominence in recent years, driven by the desire for robots to work more closely with humans to improve work productivity. This class of actuators work to vary the dynamical characteristics of robots during operation, allowing them to be more pliant when executing high-speed manoeuvres while remaining stiff and firm for tasks requiring precision, helping robots satisfy the necessary safety requirements for operating in close quarters with human workers without sacrificing too much of their performance.